2022
DOI: 10.3390/ijerph192114372
|View full text |Cite
|
Sign up to set email alerts
|

How Do Different Urban Footpath Environments Affect the Jogging Preferences of Residents of Different Genders? Empirical Research Based on Trajectory Data

Abstract: In recent years, the impact of the urban environment on residents’ physical activity (PA) has received extensive attention, but whether this impact has differences in the jogging preferences of residents in different footpath environments and different genders requires further research. Therefore, based on jogging trajectory data, this paper uses the grouping multiple linear regression model to study the different influencing factors of different footpath environments on the jogging of residents of different g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Air quality, temperature, connectivity, vibrancy, vertical elements, culture, buildings, and service facilities are less emphasized and exhibit significant variation across different land uses. Specific factors such as air quality [20], temperature [63], connectivity [28], culture [57], architecture [64], and service facilities [15] have been the focus of detailed studies, yet their impact appears limited to a few land use types compared to other factors. Thus, these factors warrant careful consideration in the decision-making process for environmental improvement.…”
Section: Environmental Preferencementioning
confidence: 99%
“…Air quality, temperature, connectivity, vibrancy, vertical elements, culture, buildings, and service facilities are less emphasized and exhibit significant variation across different land uses. Specific factors such as air quality [20], temperature [63], connectivity [28], culture [57], architecture [64], and service facilities [15] have been the focus of detailed studies, yet their impact appears limited to a few land use types compared to other factors. Thus, these factors warrant careful consideration in the decision-making process for environmental improvement.…”
Section: Environmental Preferencementioning
confidence: 99%
“…Lighting facilities, pavement, and vertical elements describe facilities intrinsic to the jogging routes [3,55]. Residential areas, campuses, sports facilities, and commercial areas characterize the surrounding environment [20,37]. Safety and accessibility frequently serve as indicators in the jogging studies literature [24,56].…”
Section: Measuring Efpai Through Text Analysismentioning
confidence: 99%
“…In recent years, the impact of the street environment on jogging has increasingly gained attention. Studies have explored both linear [2,20] and nonlinear [21][22][23] correlations between various environmental factors and jogging behavior, including but not limited to traffic facilities [2,24], natural exposure [2,25], accessibility [12], and climate [26]. However, many environmental factors used in research are pre-selected based on expert experience and previous literature [27,28], potentially overlooking or neglecting factors that joggers focus on.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the concept of "street" has been rather vague in many recent studies. Zhong et al (2022) identified three types of streets: "urban sidewalks," "community sidewalks," and "green space sidewalks," and discovered that the three distinct street environments had different impacts on people and that various environmental elements have different positive and negative impacts on residents [51]. Hence, to apply these findings to specific street types, as in Zhang et al (2022), we first categorized urban streets into three types: community streets (built environment), waterfront paths (built environment with water elements), and urban greenways (built environment with green elements) [51].…”
Section: Research Questionsmentioning
confidence: 99%